the structure of summary and detail in the holy Quran: textual approach - Jabbar, Nisreen (Al-Adab Journal, 2025)
The relationship of generality - detail is one of the relationships that is closely related to textual cohesion because it is one of the semantic relationships that the text occupies to connect sections with each other by continuing a certain meaning in those sections. This relationship was achieved through three main ingenious observations: -Division, combination, differentiation. They all have one semantic function because they come together in one style that reveals the movement of analyzing a specific thing into multiple elements or collecting multiple elements into one thing. The research dealt with Qur’anic surahs that spoke about the Day of Resurrection, so the unification of their subject matter allowed them to possess a single higher structure and for the presence of structural interconnection and semantic interconnection. Between the verses of those surahs, they became as if they were one text and tightly woven together, and the research was divided into an introduction and three sections, followed by a conclusion and supported by sources.